2020
DOI: 10.1088/1751-8121/abcc84
|View full text |Cite
|
Sign up to set email alerts
|

Empirical anomaly measure for finite-variance processes

Abstract: Anomalous diffusion phenomena are observed in many areas of interest. They manifest themselves in deviations from the laws of Brownian motion (BM), e.g. in the non-linear growth (mostly power-law) in time of the ensemble average mean squared displacement (MSD). When we analyze the real-life data in the context of anomalous diffusion, the primary problem is the proper identification of the type of the anomaly. In this paper, we introduce a new statistic, called empirical anomaly measure (EAM), that can be usef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…Since each of these models describes different physical causes for anomalous diffusion, identifying the best-fitting stochastic model is an important step in unraveling the physical origin of an experimentally observed anomalous diffusion. , , Similarly determining specific parameters attributed to each model, such as the anomalous diffusion exponent α and coefficient K α , can help quantify and/or differentiate between trajectories or systems. , Typically this task is tackled through the use of statistical observables, aiming at quantifying the expected differences between the models. ,− However, the stochastic nature of these models in combination with the often noisy and limited experimental data can severely hinder this process and may lead to conflicting results from different observables. For example, it has been shown that noisy data can lead to a mistaken identification as subdiffusion. , …”
Section: Classical Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…Since each of these models describes different physical causes for anomalous diffusion, identifying the best-fitting stochastic model is an important step in unraveling the physical origin of an experimentally observed anomalous diffusion. , , Similarly determining specific parameters attributed to each model, such as the anomalous diffusion exponent α and coefficient K α , can help quantify and/or differentiate between trajectories or systems. , Typically this task is tackled through the use of statistical observables, aiming at quantifying the expected differences between the models. ,− However, the stochastic nature of these models in combination with the often noisy and limited experimental data can severely hinder this process and may lead to conflicting results from different observables. For example, it has been shown that noisy data can lead to a mistaken identification as subdiffusion. , …”
Section: Classical Approachmentioning
confidence: 99%
“…The aforementioned methods cover only a fraction of possibilities. Other techniques not further specified here include the use of the velocity autocorrelation, the first passage statistics, the codifference, or the autocovariance . The applications of these statistical techniques, however, struggle when data is sparse and often require an ensemble of trajectories. , …”
Section: Classical Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Transient anomalous diffusion is also obtained in a tempered fractionally integrated process [33]. Maraj et al [34] introduces the empirical anomaly measure as a means to measure the distance between the anomalous diffusion process and normal diffusion. Limit properties of Lévy walks are shown to be useful in the recognition and verification of Lévy walk-type motion, as well as the parameter estimation in maximum likelihood methods [35].…”
Section: Introductionmentioning
confidence: 99%
“…Ref. [33] introduces the empirical anomaly measure as a means to measure the distance between the anomalous diffusion process and normal diffusion. Limit properties of Lévy walks are shown to be useful in the recognition and verification of Lévy walk-type motion, as well as the parameter estimation in maximum likelihood methods [34].…”
Section: Introductionmentioning
confidence: 99%